Sulfur isotopes, trace element, and textural analyses of pyrite, arsenopyrite and base metal sulfides associated with gold mineralization in the Pataz-Parcoy district, Peru: implication for paragenesis, fluid source, and gold deposition mechanisms - Voute, F.; Hagemann, S.; Evans, Noreen; Villanes, C. (Springer, 2019)
In the Pataz-Parcoy district, current mining activity is focused on the mesothermal quartz-carbonate-sulfide veins hosted by the Pataz batholith. Total gold production yielded approximately 8 Moz with grades in the mined ore shoots varying between 7 and 15 g/t Au, and locally reaching up to 120 g/t Au. High-grade ore shoots are extraordinarily enriched in sulfides, representing 10 to 20 modal vol% of the vein. Ore mineralogy is characterized by a complex paragenesis of pyrite, arsenopyrite, galena, sphalerite, chalcopyrite, and gold. Gold occurs mostly as electrum in equilibrium with base metals sulfides filling fractures of pyrite and arsenopyrite. A novel combination of secondary ion mass spectrometry, laser ablation inductively coupled plasma mass spectrometry, and electron probe microanalysis is used to track the compositional evolution of ore fluid(s) and to investigate the mineralization processes occurring in the Pataz-Parcoy district. Contrasting with the classical two-stage ore sequence previously proposed for the Pataz-Parcoy district, we suggest a revised paragenetic sequence, i.e., (1) deposition of pyrite core (PyI) with homogeneously distributed base metal sulfide inclusions, (2) progressive replacement of PyI by arsenian pyrite (PyII) and arsenopyrite associated with invisible gold deposition, and (3) deposition of sphalerite – galena ± chalcopyrite - electrum in fractured pyrite and arsenopyrite. We propose two models for the formation of base metal sulfide inclusions in PyI, i.e., (1) co-precipitation of base metal sulfide with PyI and later redistribution in cracks driven by partial As replacement of PyI to PyII and arsenopyrite and (2) preferential replacement of the PyI along crystallographic planes by percolation of the fluid responsible for base metal sulfide deposition in fractured pyrite and arsenopyrite.